The Effect of Ethanolic Extract of Brazilian Green Propolis and Artepillin C on Cytokine Secretion by Stage IV Glioma Cells Under Hypoxic and Normoxic Conditions - Małgorzata Kłósek; Anna Kurek-Górecka; Radosław Balwierz; Grażyna Pietsz; Zenon P. Czuba (Pharmaceuticals)
Background: The majority of gliomas are astrocytic in nature. Gliomas have the lowest survival rate among all tumors of the central nervous system (CNS), characterized by high aggressiveness and poor response to treatment. The tumor microenvironment is a source of cytokines such as IL-6, IFN-γ, VEGF, and PDGF-BB, secreted mainly by tumor and immune cells. These cytokines play a significant role in angiogenesis, invasion, and metastasis formation. In vitro and in vivo studies have shown that Brazilian green propolis, derived from Baccharis dracunculifolia DC and rich in artepillin C, exhibits anti-inflammatory, antimicrobial, chemopreventive, and anticancer activities. Additionally, it can penetrate the blood–brain barrier, demonstrating neuroprotective effects. The aim of the present study was to determine the concentration of selected cytokines produced by astrocytes of the CCF-STTG1 cell line, isolated from the brain of a patient with stage IV glioma (astrocytoma). Methods: The cytotoxicity of the EEP-B was evaluated using the MTT assay. Astrocytes were stimulated with LPS at a final concentration of 200 ng/mL and/or IFN-α at 100 U/mL, followed by incubation with EEP-B (25–50 µg/mL) and artepillin C (25–50 µg/mL) under 2-h hypoxia and normoxia conditions. Cytokine concentrations were measured using the xMAP Luminex Multiplex Immunoassay and the Multiplex Bead-Based Cytokine kit. Results: The absence of cytotoxic effects of EEP-B and artepillin C on human astrocytes of the CCF-STTG1 lineage was demonstrated. Stimulation with LPS, IFN-α, and their combination (LPS + IFN-α) significantly increased the secretion of the tested cytokines compared to the control cell line. The most pronounced and statistically significant reduction in cytokine levels, particularly IL-6 and VEGF, was observed following EEP-B treatment at both tested concentrations under both hypoxic and normoxic conditions. Conclusions: Brazilian green propolis may serve as a potential immunomodulator in combination therapies for gliomas of varying malignancy grades.